How Many Calories Does Physical Activity Require for Physical Education College Students? - Muhammad Saleh; Wening Nugraheni; Bachtiar Bachtiar; Leo Pratama; Tariza Sagita Hermawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The energy needs of each student vary depending on the type of activity of each because the task of students is not only to study but also as athletes, instructors, coaches, teachers or office workers. So that the energy needs of each student will be even if it is not known. Energy is the body's ability for physical activity. To be able to carry out physical activities optimally, sufficient energy is needed. This study aims to know early on the energy needs of students' physical activity. This research uses a quantitative descriptive method with a cross-sectional approach. Respondents in this research were 26 students, 18 men and 8 women, using the total sampling technique. This study uses a survey method. The instruments used in data collection were Body Mass Index (BMI), Basal Metabolic Rate (BMR), Specific Dynamic Action (SDA), Daily Activity Energy, and Exercise Energy. Data analysis uses percentages, max, min, and average values. The results of the study stated that the average BMI for the male sex was 11 respondents with the normal weight category and the average MBI for the female sex was 7 respondents with the normal weight category. So, student BMI in general is in the Normal Weight classification. While the average energy requirement for male students is 3217 cal/day, and the average energy requirement for female physical activity is 2466 cal/day, then the average activity carried out is study, practice and work. In conclusion, the energy requirements needed by male and female physical education students average 2985 cal/day, with the most frequent and average activities carried out being study and practice.